2021
DOI: 10.5114/reum.2021.107026
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tocilizumab for rheumatoid arthritis: a systematic review and metaanalysis of clinical trial studies

Abstract: The present systematic review and meta-analysis was conducted to assess the effect of tocilizumab (TCZ) in patients with rheumatoid arthritis (RA). We systematically searched all potential articles in the main databases, including PubMed, Scopus, EMBASE, Web of Sciences (ISI), and Cochrane Center. The search was subsequently updated in December 2020. The initial review and extraction of information were performed independently by two authors to collect the first author and publication year; sample size; mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(81 reference statements)
1
3
0
1
Order By: Relevance
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA 36–38 . The long‐term safety profile of tocilizumab (mean treatment duration, 2.4 years) from several phase III trials and open‐label extensions did not demonstrate an increase in serious or treatment‐related AEs, and the data were overall consistent with those of post‐marketing trials and clinical experience 39 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA 36–38 . The long‐term safety profile of tocilizumab (mean treatment duration, 2.4 years) from several phase III trials and open‐label extensions did not demonstrate an increase in serious or treatment‐related AEs, and the data were overall consistent with those of post‐marketing trials and clinical experience 39 .…”
Section: Discussionsupporting
confidence: 85%
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA. [36][37][38] The long-term safety profile of tocilizumab (mean treatment duration,…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of infections, particularly serious or opportunistic infections, are one of the most significant risks associated with TCZ. Patients taking TCZ are, therefore, more susceptible to infections such as pneumonia, sepsis, and tuberculosis (16). Our data withal revealed that patients with comorbidities had worsened prognostic laboratory results.…”
Section: Discussionmentioning
confidence: 51%
“…Newer bDMARDs, with various modes of action, can be administered to RA patients who are unresponsive to TNF-inhibitor treatment [ 54 ]. For instance, abatacept (ABT, which interrupts the costimulation molecule signal between T and B cells) [ 55 ], rituximab (RTX, which targets CD20 + B cells) [ 56 ], and tocilizumab (TCZ, which is an IL-6 receptor (IL-6R) antagonist) [ 57 ] have demonstrated high treatment efficacy in patients with active RA, particularly in those with inadequate responses to TNF-inhibitor treatment [ 58 ].…”
Section: Current Therapy For Ramentioning
confidence: 99%